Effects of liquid pig manure fertilization on the density and species structure of Oribatida (Acari) and green forage yield in a lowland meadow in Poland - Wasińska-Graczyk, Beata; Seniczak, Stanisław; Graczyk, Radomir (Biological Letters, 2010)
The effect of liquid pig manure fertilization, with or without the disinfectant VIT-TRA, on oribatid communities was investigated in a lowland meadow in Poland. The disinfectant was tested at 3 concentrations: 0.50% (fungicidal), 0.75% (bactericidal), and 3.00% (viricidal). Liquid pig manure without the disinfectant increased the green forage yield along with increasing doses of this fertilizer, while addition of disinfectants affected the yield in different ways. Low and medium doses of fertilizer (20 and 40 m3·ha-1) with fungicide slightly decreased the yield, while the high dose (60 m3·ha-1) usually increased it, as compared to the control. Low and medium doses of liquid pig manure, treated or not with disinfectants, decreased the abundance of oribatid mites. In contrast, the high dose increased their abundance, except for the plot with a high dose of viricide, where they were slightly less abundant than in the control. In the investigated meadow, Liebstadia humerata, Parachipteria bella and Scheloribates laevigatus were abundant, but reacted negatively to low and medium doses of liquid pig manure treated or not with disinfectants, and positively only to the high dose of fertilizer treated with fungicide and bactericide, as compared to the control plot.